Investigation of flow over textured surfaces - Thong, Jacinta Jia Wei (2017)
Achieving drag reduction in fluid flow has been one of the main aims of engineers in the field of fluid mechanics. Surfaces with biomimetic structures have shown to successfully reduce drag for water and air flow. Furthermore, superhydrophobic surfaces created by using sandpaper to manually sand Teflon plates, managed to achieve drag reduction in water flow. However, studies using air as the fluid medium have not been carried out. Thus, this study aims to determine if manually sanded Teflon surfaces can also provide a drag reduction benefit for air flow. A total of 20 samples, including one control, was investigated in this study. The sanding method parameters that were varied were the sandpaper grit designation of the sandpaper, the sanding duration, the sanding direction and whether the sample was sanded twice with different sandpaper grit designations. A test rig was designed and fabricated such that the pressure drop across the Teflon sample as air flowed over it could be measured with a differential manometer. Out of all the sandpaper grit designation investigated in this study, it was found that the 24-grit sandpaper provided the best pressure drop reduction benefit. For sanding duration, the drag reduction benefit for samples sanded for 1.5 minutes triumphed over all the other durations investigated in this study. Also, sanding preferentially in the flow direction as compared to the circular or cross-flow direction proved to be better in terms of drag reduction benefit. In addition, even better pressure drop reduction was achieved when the Teflon sample was sanded twice with different sandpaper in the flow direction. This could be because sanding in the flow direction create grooves that promote anisotropic flow and double sanding has been observed to reduce the height of the grooves, which could decrease the wetted surface area of the sample. Overall, the Teflon sample that provided the best pressure drop reduction benefit was the 24 + 240 grit sample.